(untitled) (Central Asian Journal of Medical Sciences, 2016)
Objectives: Skin is a primary epithelial organ, which protects our body from the surrounding environment. Besides physical barrier machineries, skin also contains a number of immune components that actively participate in the protective immune responses. Dendritic cells (DCs) are professional antigen-presenting cells and they are essentially required for mediating innate and adaptive immunity. Although emerging studies have demonstrated distinct resident DC subsets in the skin, their subset-specific functions still need to be elucidated. Methods: We reviewed recent works on the DC subset discrimination and specification in the mouse skin. To understand the DC subset-dependent functional diversity, we especially focused on the murine contact hypersensitivity (CHS), an experimental model of human allergic contact dermatitis. Furthermore, we discussed our recent work on the role of epidermal Langerhans cells (LCs) in CHS. Results: Murine skin harbors at least three DC subsets: (i) epidermal LCs, (ii) Langerin+ dermal DCs and (iii) Langerin- dermal DCs. Using more sophisticated cell markers, recent study has described monocyte-derived DCs in the skin. The role of each DC subset in CHS was somewhat inconsistent and redundant from study to study and needs further elaborative works for the general acceptance. Conclusion: Continuous efforts to understand the functional diversity among each cutaneous DC subset will be needed to develop the new anti-inflammatory and anti-tumor strategies by targeting relevant skin DC population in vivo.